1998
DOI: 10.1089/clm.1998.16.61
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy (PDT) in the Treatment of Patients with Resistant Superficial Bladder Cancer: A Long Term Experience

Abstract: PDT using 1.5 mg/kg of Photofrin and 15 J/cm2 of light (630 nm) should be considered a safe and effective treatment for refractory CIS or recurrent papillary TCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(78 citation statements)
references
References 18 publications
1
73
0
4
Order By: Relevance
“…Transitional cell carcinoma (TCC) of the bladder can efficiently be treated with this type of therapy because, with careful control of the light distribution, curative doses can reach all parts of the urothelium (5)(6)(7). This is of importance in problematic superficial tumors, which are often multifocal.…”
Section: Introductionmentioning
confidence: 99%
“…Transitional cell carcinoma (TCC) of the bladder can efficiently be treated with this type of therapy because, with careful control of the light distribution, curative doses can reach all parts of the urothelium (5)(6)(7). This is of importance in problematic superficial tumors, which are often multifocal.…”
Section: Introductionmentioning
confidence: 99%
“…These complications were associated with excessive light doses and nonuniform light delivery in the early studies. Nseyo et al showed that, for standardized protocols using lower drug and light dose [53], or for illumination with less penetrating light of 514 nm, good tumor response rates could be achieved for superficial lesions without transmural bladder injury or treatment-related morbidity [54]. Whole-bladder PDT with green light and proper dosimetry remains an attractive treatment option for carcinoma in situ (CIS), although this has not been fully evaluated.…”
Section: Bladder Cancermentioning
confidence: 99%
“…7 Additionally, PDT agents have the potential to act as multifunctional theranostic agents to achieve simultaneous monitoring and therapeutic capabilities during cancer treatment. 8,9 For these reasons, PDT has emerged as an important therapeutic option in the management of cancers, such as early lung cancer, 10 Barrett's esophagus, 11 bladder cancer, 12 head and neck cancers, 13 skin cancer, 14 and bronchial cancers. 15 The essential element for effective PDT is an ideal PS, the lack of which continues to be a major roadblock restricting the clinical utility of PDT as a first-line treatment option.…”
Section: Introductionmentioning
confidence: 99%